Application of Unified Power Flow Controller to Improve Steady State Voltage Limit - Samina. E. Mubeen; Baseem Khan; R. K. Nema (Institute of Advanced Engineering and Science, 2017)
This paper utilizes the voltage source model of Unified Power Flow Controller (UPFC) and examines its abilities in mitigating the steady state stability margins of electric power system. It analyzes its behavior for different controls strategies and proposes the most efficient mode of controlling the controller for voltage stability enhancement. A systematic analytical methodology based on the concept of modal analysis of the modified load flow equations is employed to identify the area in a power system which is most prone voltage instability. Also to identify the most effective point of placement for the UPFC, a computer program has been developed using MATLAB. The results of analysis on 14 bus system is presented here as a case study.